Plant Nutrient Uptake and Soil Nutrient Dynamics under Full and Limited Irrigation and Rainfed Maize Production. (1st March 2013) - Djaman, K.; Irmak, S.; Martin, D. L.; Ferguson, R. B.; Bernards, M. L.
Abstract : Limited knowledge and data exist in terms of how the soil water status affects plant nutrient uptake and the availability of soil residual nutrients in order to establish effective fertilizer management under limited irrigation to prevent undesirable environmental impacts. Maize ( Zea mays L.) nutrient uptake and concentrations of soil nutrients (N, P, and K) were measured under full and limited irrigation regimes and rainfed conditions. Fully irrigated treatment (FIT), 75% FIT, 60% FIT, 50% FIT, and rainfed treatments were imposed. Seasonal (emergence to physiological maturity) rainfall was 426 mm (18% below normal) in 2009 and 563 mm (9% above normal) in 2010. Irrigation regimes impacted nutrient uptake, with 60% and 75% FIT resulting in efficient and comparative performance relative to FIT. Nitrogen, P, and K uptake increased with water supply. Total N uptake ranged from 154 kg ha −1 for rainfed to 253 kg ha −1 for FIT in 2009 and from 182 kg ha −1 for rainfed to 270 kg ha −1 for FIT in 2010. The FIT had the greatest P uptake (39 kg ha −1 in 2009 and 53 kg ha −1 in 2010). Total grain N uptake was 143, 203, 216, 205, and 215 kg ha −1 in 2009 and 151, 178, 188, 193, and 209 kg ha −1 in 2010 for rainfed, 50% FIT, 60% FIT, 75% FIT, and FIT, respectively. The residual soil N averaged 77.5 kg ha −1 in 2009 and 72.4 kg ha −1 in 2010 and increased with irrigation. Relationships among plant N, P, and K concentrations were developed for within‐season nutrient diagnosis in practical applications.